ANALISIS PEMANFAATAN PERANGKAT CROMEBOOK DALAM PROSES PEMBELAJARAN PADA PESERTA DIDIK KELAS V SD NEGERI 03 TIUMANG - Suraya, Anti; Wiwik Okta Susilawati; Nanik Setiawati (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
This research analyzes the utilization of Chromebook devices in the learning process for fifth-grade students at SD Negeri 03 Tiumang. The background of this study is the importance of adapting education to the 4.0 industrial revolution era, especially in using technology to enhance learning quality. Chromebooks, as web-based devices developed by Google, are considered to have great potential to support digital learning, both online and offline, with cloud-based data. This research employed a qualitative approach with a field study design. Data were collected through observation, interviews with the school principal, fifth-grade teachers, and fifth-grade students, as well as documentation and questionnaires. The subjects of the study were fifth-grade students at SD Negeri 03 Tiumang, with subject selection using a purposive sampling method. The data analysis techniques used were data reduction, data display, and conclusion drawing, following the Miles and Huberman model. Data validity was tested using source triangulation. The research results indicate that the utilization of Chromebook devices at SD Negeri 03 Tiumang has yielded significant positive impacts. Chromebooks are used almost daily for various subjects, not limited to specific ones. Students feel more comfortable, find it easier to understand learning materials, and are motivated to learn due to the freedom to choose their learning styles and access to various interactive applications such as Canva, Google Classroom, Google Docs, Google Slides, and Gemini. Interaction between teachers and students, as well as among students themselves, has also increased. This utilization aligns with the Technology Acceptance Model (TAM), which emphasizes the benefits and ease of use of technology. Nevertheless, there are some challenges, particularly concerning internet connectivity, which does not yet fully support simultaneous Chromebook use, and the need for continuous training for all teachers to obtain Google Certified Educator certification. The success of Chromebook utilization has also led to SD Negeri 03 Tiumang being selected as a Google Reference School Candidate (KSRG) in Dharmasraya Regency, demonstrating an improvement in school quality in rural areas.